PENGUKURAN INTERNALISASI NILAI BUDAYA DAN INDEX SPIRITUAL (STUDI KASUS PERUSAHAAN BUMN DI INDONESIA) - Dwitya Agustina (Jurnal Ilmu Manajemen & Ekonomika, 2015)
Great companies consider knowledge or special skills are important. They assume that knowledge and expertise can be learned, while the dimensions related to convictions such as character, work ethos, dedication to fulfill the commitment, its much deeper and more difficult to modify.In one of the Indonesian corporate, the Human Capital division divided three levels of management: Character or Spiritual Level that speaks in the spirit of landscape, the level of Competence or emotional & intellectual; the area is a sense and ratio, and the level of Compensation or a physical level to talk about physical.A research method used to perform analyze of internalization corporate and spiritual index is descriptive method. Data collected from total respondents of 7061 employees by interview, study literature and questioner distribution.Result of the research is the level internalization values on a basic belief having value of 79, 81 % are on good category. Where the value on each sub-division variabel namely integrity of 80,75 %, enthusiasm of 79,61 %, and totality of 79,06 %. Based on the data to scatter the age of work, can be known that the employees with aged more than 45 years having the level of internalization of the spiritual index most higher than at the age of other working groups.Keywords: Descriptive Research, Internalization, Interview Method, Spiritual Index